2017
DOI: 10.5958/0974-8164.2017.00011.9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated weed management in Kharif blackgram

Abstract: A field experiment was conducted on medium black calcareous clayey soil at Pulses Research Station, Junagadh Agricultural University, Junagadh during three seasons of 2011-12, 2012-13 and 2014-15 to study the efficacy of pre-and post-emergence herbicides in Kharif blackgram (cv. GU-1). The quizalofopethyl 40 g/ha as post-emergence (PoE) at 20 days after seeding (DAS) + hand weeding (HW) at 40 days after seeding (DAS) and pendimethalin 900 g/ha as pre-emergence (PE) + hand weeding (HW) at 40 DAS were found equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Higher gross returns along with the lowest cost under treatments T 1 , T 3, T 4 , T 5 and T 6 might be responsible for higher net return and B: C ratio. This is in conformity with the findings of Kumar et al, (2012), Mishra et al, (2012), Priya and Kubsad (2013), Patel et al, (2014) and Thakur et al, (2016).…”
supporting
confidence: 82%
“…Higher gross returns along with the lowest cost under treatments T 1 , T 3, T 4 , T 5 and T 6 might be responsible for higher net return and B: C ratio. This is in conformity with the findings of Kumar et al, (2012), Mishra et al, (2012), Priya and Kubsad (2013), Patel et al, (2014) and Thakur et al, (2016).…”
supporting
confidence: 82%
“…moisture, nutrient, light and space resulting in higher number of weeds and dry weed biomass. Earlier workers (Priya and Kubsad 2013 and Patel et al 2014) have also reported the same for unweeded control treatment.…”
Section: Weed Density Biomass and Weed Control Efficiencysupporting
confidence: 61%
“…Patel et al (2006) has justified the similar results in maize crop with the longer persistence of atrazine and pendimethalin up to harvest of crop. While, the similar efficacy of preemergence herbicide with one hand weeding or interculturing in sorghum are supported by Kumar et al (2012), Priya and Kubsad (2013) and Patel et al (2014).…”
Section: Weed Density Biomass and Weed Control Efficiencymentioning
confidence: 74%
“…Cynodon dactyon, Dactylactenium aegyptium, Cyperus rotundus, Cyperus iria, Amaranthus viridis, Digera arvensis and Parthenium hysterophorus were Predominant weed species. The observations on these weed species during the investigation followed similar trend with those reported by Jakhar et al (2015) and Patel et al (2017).…”
Section: Weed Florasupporting
confidence: 87%